Problematika Pembelajaran Akidah Akhlak Di SD 067098 Medan Timur - Tsania, Ulfa; Nurhaliza, Nurhaliza; Sundari, Krenniti (Yayasan Rahmat Islamiyah, 2024)
There will always be problems in the learning process. The reason is due to problems in providing teaching materials to teachers and students as well as inadequate equipment. At Elementary School 067098, many problems in studying moral beliefs are caused by a lack of enthusiasm in studying moral beliefs. There are still students who are less active, bored when following the learning process, do not pay attention to the teacher's lectures, and are indifferent to the assignments and grades given. This research is a qualitative descriptive study. Data is collected in word form. In this case, it illustrates the Aquidah's problems regarding moral learning. Researchers collected data through interviews, documents and field notes. Data was analyzed through three stages, namely data reduction, data presentation, and data validation. Techniques for ensuring data validity are source triangulation, technical triangulation, and time triangulation. Based on the results of the researchers, the following conclusions can be drawn: (1) The moral theology learning process at Elementary School 067098 is still in the development stage and is one of the best processes that we are trying to achieve. In providing facilities and infrastructure to support the learning of moral theology Elementary School 067098, the problem of learning moral theology Class is seen from two factors. So, first of all, these are internal factors, common problems. With teachers and students. The problem of Aqidah Ethics for Teachers is to convince children about the supernatural and real Islamic Aqidah especially the belief that students cannot concentrate when studying and often feel bored and sleepy during lessons. Problems caused by external factors, especially the mismatch between moral belief learning material and its application at school, at home and in the community. (3) Overcoming problems caused by internal factors, especially teachers' efforts to overcome problems by further improving their abilities, carrying out MGMP activities, and remaining active in communicating with students.